Outcome of resection and primary anastomosis of colon upto the level of the rectosigmoid junction without diverting ileostomy or colostomy in Dhaka Medical College Hospital-a study of 50+ cases - Dutta, Surajit; Sultana, Salma; Nath, Sukla; Al Masud, A. K. M.; Haque, Aminul; Mondal, M. Fahimul Islam; Alam, Noor-E; Mahmud, Sakit; Hoque, Mohammed Aynul; Al Mamun, Abdullah; Hossain, M. Shahid (International Surgery Journal, 2025)
Background: Colon resection is frequently performed in surgical practice for various indications. A key decision is whether to perform primary anastomosis with or without proximal diversion. Although diversion adds safety, it also introduces additional complications. In Bangladesh, outcomes of primary anastomosis without diversion have not been systematically studied. To evaluate the outcomes and safety of colon resection with primary anastomosis, without diverting ileostomy or colostomy, in both emergency and elective surgical cases. Methods: This descriptive cross-sectional study included 52 patients who underwent colon resection up to the rectosigmoid junction with primary anastomosis, without diversion, in the Department of Surgery, Dhaka Medical College Hospital, from January 2013 to September 2013. Patients over 12 years of age, regardless of sex, meeting specific inclusion and exclusion criteria were enrolled. Data on demographic profile, surgical indication, intraoperative findings, postoperative outcomes and complications were collected and analyzed using SPSS. Results: Among the 52 patients (age range: 19–75 years), the majority were male (75%) and over 50 years of age. The most common indication for surgery was sigmoid volvulus. Emergency colectomy was performed in 53.85% of cases. In 86.54% of cases, the resected bowel was viable and single-layer anastomosis was the preferred technique. Postoperative blood transfusion was frequently required. Early oral intake was resumed in 55.77% of patients. There was no mortality and 82.69% of patients experienced no postoperative complications. Most patients were discharged within 13–14 days. Conclusions: This study demonstrates that resection with primary anastomosis of the colon up to the rectosigmoid junction without a diverting ileostomy or colostomy is a safe and effective option in both elective and emergency surgical settings when proper patient selection and operative techniques are employed.